2014
DOI: 10.1177/0959683614551223
|View full text |Cite
|
Sign up to set email alerts
|

Coastal palaeoenvironmental record of the last 7 kyr BP in NW France: Sub-millennial climatic and anthropic Holocene signals

Abstract: et al.. Coastal palaeoenvironmental record of the last 7 kyr BP in NW France: Sub-millennial climatic and anthropic Holocene signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 64 publications
1
25
0
Order By: Relevance
“…The GL marsh is therefore a perfect area to perform paleoenvironmental studies of the Holocene period using comprehensive sediment records. Additionally, several studies conducted around Brittany previously confirmed that coastal environments represent pertinent and key study areas to decipher Holocene climatic and/or anthropogenic changes (Sorrel et al, 2009(Sorrel et al, , 2012Baltzer et al, 2014;Fernane et al, 2014;Van Vliet-Lanoë et al, 2014).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…The GL marsh is therefore a perfect area to perform paleoenvironmental studies of the Holocene period using comprehensive sediment records. Additionally, several studies conducted around Brittany previously confirmed that coastal environments represent pertinent and key study areas to decipher Holocene climatic and/or anthropogenic changes (Sorrel et al, 2009(Sorrel et al, , 2012Baltzer et al, 2014;Fernane et al, 2014;Van Vliet-Lanoë et al, 2014).…”
Section: Introductionmentioning
confidence: 88%
“…Dark-gray bands represent sandy facies where no palynological studies have been conducted, a major sediment hiatus in Pors Milin related to the breaching of sandy dunes is recorded during the Bronze Age (cf. Fernane et al, 2014).…”
Section: Forcing Factors Responsible For Human Settlement and Departumentioning
confidence: 95%
See 2 more Smart Citations
“…19 past human agricultural practices since the Neolithic (e.g. Fernane et al, 2014). Their general underrepresentation in modern BB sediments must be kept in mind when considering…”
Section: Accepted Manuscriptmentioning
confidence: 99%